KOMUNITAS MOLUSKA DI PADANG LAMUN PANTAI WORI, SULAWESI UTARA - Arbi, Ucu Yanu (Bumi Lestari; Vol 12 No 1 (2012), 2012)
Observation on molluscs on seagrass beds ecosystem of Wori waters, North Sulawesi was conducted on April and June 2008. Seagrass beds of Wori waters has a good condition. Molluscs as one of occupier marine live in seagrass beds. The observation was aimed to get an idea on the condition of molluscs at seagrass beds ecosystem of Wori waters. It was made at 7 stations of 3 location. Molluscs samples in quadrant transect line from the edge of the beach to the sea were counted and identified. 634 individual from 163 species of molluscs was identified consist of 125 species Gastropoda and 38 species Pelecypoda. Pyrene scripta (Columbellidae) Vexillum plicarium (Costellariidae), Cypraea annulus (Cypraeidae) and Strombus urceus (Strombidae) class of Gastropoda were the common and widely distributed molluscs. Molluscs community on seagras beds of Wori waters on medium diversity. The highest diversity index (H) (1.62) was found at Station 7 and the lowest (1.303) was found at Station 4. An evenness index (J) was 0.841 to 0.969 and richness index (D) was 70.673 to 107.63.
Keywords: molluscs community, seagrass beds, Wori beach, North Sulawesi